Complications of Carotid Blowout Syndrome in Patients with Head and Neck Cancers Treated by Covered Stents - Chang, Feng-Chi (Centauro S.r.l., 2008)
The purpose of this study was to improve clinical assessment of carotid-blowout syndrome (CBS) in patients with head-and-neck cancers and with covered stents by evaluating immediate and delayed complications of reconstructive management. Eleven such patients were treated with self-expandable covered stents. We evaluated immediate and delayed complications by assessing clinical and imaging findings. Technical success and immediate hemostasis were achieved in all patients. Immediate complications were noted in four patients (36.4%), including thromboembolism in three patients and, in one patient, dissection of the carotid artery and type III endoleak by the overlapped self-expandable stent causing rebleeding. Delayed complications were noted in eight patients (72.7%), including six episodes of rebleeding in five patients, distal marginal stenosis in five patients, and delayed carotid thrombosis in three patients (one with brain abscess formation). We suggest close follow-up of the patients and aggressive re-intervention of their complications to improve outcomes.